2017
DOI: 10.1097/qai.0000000000001151
|View full text |Cite
|
Sign up to set email alerts
|

Using CD4 Data to Estimate HIV Incidence, Prevalence, and Percent of Undiagnosed Infections in the United States

Abstract: HIV incidence, prevalence, and undiagnosed infections can be estimated using HIV case surveillance data and information on first CD4 test result after diagnosis. Similar to earlier findings, the decreases in incidence and undiagnosed infections are encouraging but intensified efforts for HIV testing and treatment are needed to meet the goals of the National HIV/AIDS Strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(138 citation statements)
references
References 20 publications
4
129
0
3
Order By: Relevance
“…Although the assumption that the square root of CD4 count is linearly related to time since infection has frequently been used in different settings [12,14,15], other types of functions have also been proposed [38,39]. In addition, Rice and collaborators have suggested that besides age at diagnosis, ethnicity and region of birth are significant predictors of rate of CD4 decrease [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the assumption that the square root of CD4 count is linearly related to time since infection has frequently been used in different settings [12,14,15], other types of functions have also been proposed [38,39]. In addition, Rice and collaborators have suggested that besides age at diagnosis, ethnicity and region of birth are significant predictors of rate of CD4 decrease [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, the expansion of antiretroviral therapy has lengthened the time to the onset of AIDS [10] making inferences about HIV incidence based on AIDS reported cases very limited. More recently, updates of back-calculation models relying on new HIV diagnoses have been applied for HIV incidence estimation [11][12][13][14][15]. One of the difficulties faced is to distinguish the contribution of changes in testing patterns in the trends of HIV reported cases [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New methods for estimating HIV incidence may in the future make these estimates more readily available for measuring progress in HIV prevention. (2)…”
Section: Discussionmentioning
confidence: 99%
“…(1) Estimated annual HIV incidence in 2013 was 39,000 compared with 43,200 in 2010, based on CD4 test results from people with diagnosed HIV and a CD4 depletion model. (2)…”
Section: Introductionmentioning
confidence: 99%